Development and application of crude sap-based recombinase polymerase amplification assay for the detection and occurrence of grapevine geminivirus A in Indian grapevine cultivars - Kishan, Gopi; Kumar, Rakesh; Sharma, Susheel Kumar; Srivastava, Nishant; Gupta, Nitika; Kumar, Ashwini; Baranwal, Virendra Kumar (Frontiers in Plant Science, 2023)
Geminiviruses are known to infect several fields and horticultural crops around the globe. Grapevine geminivirus A (GGVA) was reported in the USA in 2017 and since then it has been reported in several countries. Complete genome recovered through HTS-based virome analysis in Indian grapevine cultivars had all the six ORFs and a conserved nonanucleotide sequence ′5-TAATATTAC-3′ similar to all other geminiviruses. Recombinase polymerase amplification (RPA), an isothermal amplification technique was developed for the detection of GGVA in grapevine samples employing crude sap lysed in 0.5M NaOH solution and compared with purified DNA/cDNA as a template. One of the key advantages of this assay is that it does not require any purification or isolation of the viral DNA and can be performed at a wide range of temperatures (18-46 °C) and periods (10-40 minutes), which makes it a rapid and cost-effective method for the detection of GGVA in grapevine. The developed assay has sensitivity up to 0.1 fg μl-1 using crude plant sap as a template and detected GGVA in several grapevine cultivars of a major grapevine growing area. Because of its simplicity and rapidity, it can be replicated for other DNA viruses infecting grapevine and will be a very useful technique for certification and surveillance in different grapevine-growing regions of the country.